A.E. Housman papers - Housman, A. E. (Alfred Edward), 1859-1936.; Housman, A. E. (Alfred Edward), 1859-1936.; Housman, A. E. (Alfred Edward), 1859-1936.; Housman, A. E. (Alfred Edward), 1859-1936.
Chiefly notebooks containing drafts, fair copies, and fragments of Housman's poetry, most of which were published in A Shropshire Lad (1896), Last Poems (1922), and More Poems (1936). Includes a photocopy of an analysis of the poems prepared by John Carter along with an index to the original arrangement of the notebooks. Also includes photocopies of the published volumes annotated by Carter with readings from the original manuscripts as transcribed from the notebooks, correspondence, and miscellaneous papers.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
In part, photocopies.
Library of Congress Prints and Photographs Division.
English poet.
Collection material in English.
Keywords: Carter, John, -- 1905-1975.; English literature; English poetry; Literature; Poetry; Poets